Analisis Dampak Program Pelatihan Guru terhadap Kualitas Pengajaran di SMK - Enjang Suhaedin; Wike Oriza; Ambiyar Ambiyar; Fahmi Rizal (Journal on Education, 2024)
This research aims to analyze the impact of teacher training programs on improving the quality of teaching in Vocational High Schools (SMK). The research method used is a qualitative approach by collecting data through in-depth interviews, observation and document analysis from several vocational schools in Indonesia. The research results show that the teacher training program makes a significant contribution to increasing pedagogical competence, the application of technology in learning, more effective classroom management, and increasing teacher motivation and job satisfaction. Factors that influence the effectiveness of training programs include the quality of instructors, relevance of training materials, support and facilities from schools, teacher motivation, training methods, and ongoing evaluation and feedback. The relevance of training materials to teaching needs is very important to ensure that teachers acquire knowledge and skills that are in accordance with applicable curriculum requirements and competency standards. Based on these findings, it is recommended to improve the quality and competence of instructors, prepare relevant training materials, provide full support from schools, increase teacher motivation and commitment, and carry out regular evaluation and program adjustments. With these steps, it is hoped that teacher training programs in vocational schools can be more effective in improving teacher professionalism and the overall quality of education.